PENGARUH HORIZONTAL EQUITY, VERTICAL EQUITY, EXCHANGE EQUITY, DAN PROCEDURAL FAIRNESS TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA TABANAN - Khisya Wulandari; Komang Fridagustina Adnantara; Laras Oktaviani (Universitas Triatma Mulya, 2023)
One of the factors that influence taxpayer compliance is the dimension oftax justice which consists of horizontal equity or horizontal tax justice, verticalequity or vertical tax justice, exchange equity or reciprocity given by the taxauthorities to taxpayers, and procedural justice or procedural justice where if thedimension of justice taxes are implemented properly and appropriately, it willincrease taxpayer compliance. The problem in this study is whether the effect ofhorizontal equity (X1), vertical equity (X2), stock exchange equity (X3), andprocedural justice (X4) on individual taxpayer compliance at KPP PratamaTabanan. The phenomenon that occurs is a decrease in tax compliance and also taxrevenue. This research is a quantitative study, the population used is individualtaxpayers at KPP Pratama Tabanan totaling 69,609 people. The sample used was116 respondents who were determined by the convenience sampling method. Thedata analysis technique used is Multiple Linear Regression Analysis, so the resultsof the study namely Horizontal Equity Variables (X1), Vertical Equity (X2),Exchange Equity (X3), and Procedural Justice (X4) have a significant and positiveeffect on Individual Taxpayer Compliance at KPP Tabanan Primary.